2018
DOI: 10.1186/s12891-018-2228-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of fluoroscopy views and standardized procedure of percutaneous magic screw insertion for acetabulum fractures

Abstract: BackgroundTo place the magic screw more simply, we established a set of reproducible fluoroscopic views and a standardized procedure of magic screw insertion.Materials and methodsThis study on the magic screw tunnel uses a three-dimensional reconstruction model and a skeleton projection. The 3D model of the pelvis was made to be transparent and it was rotated to the place where the ischial spine was just sheltered by the posterior wall of the acetabulum. The angles of this view projection were recorded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…When using the NALP, the compression screws were driven into the anterior and posterior columns through the plate to compress the acetabular fracture ends. However, although the auxiliary insertion point was provided when the NALP was used, the correct implantation was also dependent on the combined application of the guide module and the perspective, which increased the operation time [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…When using the NALP, the compression screws were driven into the anterior and posterior columns through the plate to compress the acetabular fracture ends. However, although the auxiliary insertion point was provided when the NALP was used, the correct implantation was also dependent on the combined application of the guide module and the perspective, which increased the operation time [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Dr Tang and his team found that the narrowest diameter of the anterior column corridor for men and women is 8.59 ± 1.89 mm and 5.86 ± 1.45 mm, respectively 5 . Tang's team also established fluoroscopy views and a standardized procedure for percutaneous magic screw insertion for acetabulum fractures 8 . Chen et al .…”
Section: Introductionmentioning
confidence: 99%